2018
DOI: 10.3390/su10020464
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of CO2 Emissions Produced by Commercial Grills in Veracruz, Mexico

Abstract: Abstract:In some urban areas in Mexico, the use of firewood and charcoal as fuel for meat grills in commercial establishments, has proliferated due to economic and cultural factors. Although this activity satisfies diverse human necessities, it also generates waste that impacts the environment to local and global scales. Such is the case of CO 2 emissions produced by biomass burning in grills, whose sources are not recognized in municipal inventories of greenhouse effect gases (GEG) of the State of Veracruz. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
1
Order By: Relevance
“…The production of organic and inorganic compounds produced by incomplete combustion of biomass produced a high amount of carbon monoxide. Charcoal and firewood, the most fuel used in commercial grills fast-food, contribute to the amount of carbon-monoxide and carbon- dioxide levels ( 22 ). Another study showed the indirect effect of CO on blood parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The production of organic and inorganic compounds produced by incomplete combustion of biomass produced a high amount of carbon monoxide. Charcoal and firewood, the most fuel used in commercial grills fast-food, contribute to the amount of carbon-monoxide and carbon- dioxide levels ( 22 ). Another study showed the indirect effect of CO on blood parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Another, increasingly important source of atmospheric air pollutants including PM, carbon monoxide (CO), nitrogen oxides (NO x ), volatile organic compounds (VOCs), carbonyls, trace metals, and polycyclic aromatic hydrocarbons (PAHs) are barbecue grills powered by lump charcoal and charcoal briquettes [21][22][23][24][25][26][27]. According to the reports of Hearth, Patio and Barbecue Association almost 64% of U.S. adults own a grill, while in Canada-about 72%.…”
Section: Introductionmentioning
confidence: 99%
“…12 (2): 9-26, julio-diciembre 2020. ISSN: 1659-455X • e-ISSN: 1659-407X DOI: http://dx.doi.org/10.15359/revmar.12-2.2 Esta laguna, como otras del golfo de México, ha sido alterada por procesos climáticos, que afectan la temporalidad regional por el incremento de huracanes de gran intensidad, la erosión de playas y el cambio del nivel del mar (Lango-Reynoso et al 2019). Al mismo tiempo, las actividades humanas industriales han inducido, por ejemplo, contaminación por petróleo y la sobrepesca, por su parte, ha perturbado la integridad del ecosistema por varias décadas (Solano & Frutos, 2013;Beltrán-García et al 2019).…”
Section: Introductionunclassified